2010
DOI: 10.1183/09031936.00152609
|View full text |Cite
|
Sign up to set email alerts
|

A simple assessment of dyspnoea as a prognostic indicator in idiopathic pulmonary fibrosis

Abstract: The prognosis in idiopathic pulmonary fibrosis (IPF) is poor. No therapy has been shown to prolong survival. The objective of this study was to examine the prognostic significance of dyspnoea in daily living at baseline in IPF using a simple assessment tool.93 consecutive patients with IPF, who had undergone evaluation at diagnosis, were included. The level of dyspnoea was assessed using the modified Medical Research Council (MRC) scale. The relationship between data at baseline and survival was examined.A uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
160
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(172 citation statements)
references
References 32 publications
(50 reference statements)
5
160
5
2
Order By: Relevance
“…This feature has inadvertently not been considered by NISHIYAMA et al [1] while prognosticating regarding patients with IPF, and has possibly led to inaccurate disease assessment. Serial evaluation of dyspnoea could have solved this issue and strengthened its prognostic role, but was not carried out during the study.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…This feature has inadvertently not been considered by NISHIYAMA et al [1] while prognosticating regarding patients with IPF, and has possibly led to inaccurate disease assessment. Serial evaluation of dyspnoea could have solved this issue and strengthened its prognostic role, but was not carried out during the study.…”
mentioning
confidence: 94%
“…Mohapatra, in which they commented on our article demonstrating the relationship between daily dyspnoea and survival in idiopathic pulmonary fibrosis (IPF) [1].…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown to be related to both disease-specific and generic health-related quality of life in COPD patients (Hajiro et al, 1999), and has been shown to be a significant predictor of survival in both COPD (Nishimura et al, 2002) and idiopathic pulmonary fibrosis (Nishiyama et al, 2010), independent of lung function. It was also shown to be a significant predictor of 2-year and 10-year mortality in a population study of elderly community-dwelling adults, independent of age, gender and underlying cardiorespiratory disease (Ahmed et al, 2012).…”
Section: Relationship Between Dcs and Breathlessnessmentioning
confidence: 99%
“…It is a considerable source of psychosocial and physical stress, being associated with fear, anxiety, social isolation and functional disability (Booth et al, 2003). It has also been shown to predict mortality, independent of lung function, in a range of conditions, including COPD (Nishimura et al, 2002), pulmonary fibrosis (Nishiyama et al, 2010), and older adulthood (Ahmed et al, 2012). These effects suggest a potential role for the stress hormone system in the experience of breathlessness.…”
Section: Introductionmentioning
confidence: 99%